Impact of Gliclazide Modified Release or Glimepiride as Add-on Therapy to Metformin on Glycemic and Oxidative Stress Parameters in Type 2 Diabetic Patients - Fadhel A. Shehab; Ali L. Jasim2; Adel Gh. Mohammed (Iraqi Journal of Pharmaceutical Sciences, 2024)
Background: Type 2 diabetes mellitus is a condition characterized by an elevation of oxidative stress, which has been implicated in diabetic progression and its vascular complications.